A Fusion between Domains of the Human Bone Morphogenetic Protein-2 and Maize 27 kD γ-Zein Accumulates to High Levels in the Endoplasmic Reticulum without Forming Protein Bodies in Transgenic Tobacco - Ceresoli, Valentina; Mainieri, Davide; Del Fabbro, Massimo; Weinstein, Roberto; Pedrazzini, Emanuela (Frontiers in Plant Science, 2016)
Human Bone Morphogenetic Protein-2 (hBMP2) is an osteoinductive agent physiologically involved in bone remodelling processes. A commercialized recombinant hBMP2 produced in mammalian cell lines is available in different clinical applications where bone regeneration is needed, but widespread use has been hindered due to an unfavorable cost/effective ratio. Protein bodies are very large insoluble protein polymers that originate within the endoplasmic reticulum by prolamine accumulation during the cereal seed development. The N-terminal domain of the maize prolamin 27 kD -zein is able to promote protein body biogenesis when fused to other proteins. To produce high yield of recombinant hBMP2 active domain (ad) in stably transformed tobacco plants we have fused it to the γ-zein domain. We show that this zein-hBMP2ad fusion is retained in the endoplasmic reticulum without forming insoluble protein bodies. The accumulation levels are above 1% of total soluble leaf proteins, indicating that it could be a rapid and suitable strategy to produce hBMP2ad at affordable costs.